Perilaku Petani Terhadap Resiko Harga Cabai Merah Di Desa Kibang Kecamatan Metro Kibang Kabupaten Lampung Timur - Selvi Anggraini; Ainul Mardliyah (JURNAL WACANA PERTANIAN, 2021)
This study aims to determine the behavior of farmers to the risk of red chili prices in Kibang Village, Kibang Metro District, East Lampung Regency. The determination of this research area was done deliberately (Purposive Methode) namely in Kibang Village, Kibang Metro District, East Lampung Regency. The research method used in this study is descriptive method, and certanly equivalent. Data analysis is performed using utility functions based on the bernoulli-morgestern principle. The sampling method in this study is simple random sampling of 43 people. Farmers' behavior towards the risk of red chili prices in Kibang Village, Metro Kibang District, most farmers (81.39%) behave boldly against price risk (risk lover), 9,3% risk neutral, and 9,3% risk averter.